Penyuluhan Dan Pelatihan Instalasi Listrik Rumah Sederhana Pada Karang Taruna Muda Bestari Desa Sidodadi - Basri, Muhammad Hasan; Rifqi, Muhammad Wildan; Basri, Moh; Imaduddin, Muhammad; Abidin, Ali Zaenal; Romadhani, Muhammad Arisa; Zamani, Anwar; Jannah, Raudhatul; Dani, Irfan; Pribadi, Mahmud; Fattahillah, Achmad; Burhanuddin, Burhanuddin; Najihuddin, Ach (PT WIM Solusi Prima, 2022)
Installation of electrical installations must be considered so that in its use it does not endanger yourself or others. Therefore, the installation of electrical installations must comply with existing standards. Based on a field survey in the houses of residents of Sidodadi village, Probolinggo Regency, there are still many peeling electrical cables, improper cable connections and use of cables that are not in accordance with PUIL 2000 standards, as well as excessive load buildup on power lines so that they are prone to electrical short circuits. Therefore, Community Service (PKM) activities were carried out in Sidodadi Village which aimed to provide education to residents and youth youth groups in particular. In this JTE PKM activity it involved 15 participants consisting of residents and youth youth groups. The method used is to provide counseling and training on simple home electrical installations to residents and young bestari youth groups. This simple home electrical installation counseling and training aims to improve the knowledge, understanding and skills of the participants in the simple home electrical installation training. The results of the counseling and training on simple home electrical installations showed that 90% of participants were able to carry out simple home electrical installations properly and according to PUIL 2000 standards. Pemasangan instalasi kelistrikkan harus diperhatikan agar dalam penggunaanya tidak membahayakan diri sendiri ataupun orang lain. Oleh karena itu pemasangan instalasi kelistrikkan harus sesuai dengan standar yang ada. Berdasarkan survey lapangan pada rumah warga desa Sidodadi Kabupaten Probolinggo masih banyak ditemukan kabel listrik yang mengelupas, sambungan kabel yang tidak benar dan penggunaan kabel yang tidak sesuai dengan standar PUIL 2000, serta penumpukan beban secara berlebihan pada saluran listrik sehingga rawan terjadi korsleting listrik. Maka dari itu dilakukan kegiatan Pengabdian Kepada Masyarakat (PKM) di Desa Sidodadi yang bertujuan memberikan edukasi kepada warga serta pemuda karang taruna muda bestari khususnya. Dalam kegiatan PKM JTE ini melibatkan 15 orang peserta yang terdiri dari warga dan pemuda karang taruna. Metode yang dilakukan adalah dengan memberikan penyuluhan dan pelatihan mengenai instalasi listrik rumah sederhana kepada warga dan pemuda karang taruna muda bestari. Penyuluhan dan pelatihan instalasi listrik rumah sederhana ini bertujuan meningkatkan pengetahuan, pemahaman serta keterampilan peserta pelatihan instalasi listrik rumah sederhana. Hasil dari penyuluhan dan pelatihan mengenai instalasi listrik rumah sederhana diketahui bahwa 90% peserta sudah dapat melakukan instalasi listrik rumah sederhana dengan baik dan sesuai standar PUIL 2000.